CYBERSECURITY AND DATA PROTECTION IN THE DIGITAL AGE - Kamalova Nilufar; Toshpulatov D. A (TADQIQOTLAR, 2025)
Annotation: This article discusses the importance of cybersecurity in today’s highly digitalized world. It highlights the growing threats posed by cyberattacks and analyzes modern strategies and technologies used to protect digital information. The paper also explores challenges such as the shortage of cybersecurity specialists and the rise of artificial intelligence in both attacking and defending systems.